Efficacy of methylene blue monotherapy in semi-immune adults with uncomplicated falciparum malaria: a controlled trial in Burkina Faso - Bountogo, Mamadou; Zoungrana, Augustin; Coulibaly, Boubacar; Klose, Christina; Mansmann, Ulrich; Mockenhaupt, Frank P.; Burhenne, Jürgen; Mikus, Gerd; Walter-Sack, Ingeborg; Schirmer, Rolf Heiner; Sié, Ali; Meissner, Peter; et al. (Tropical medicine & international health, 2010)
Objective To assess the efficacy of methylene blue (MB) monotherapy in semi-immune adults with uncomplicated malaria in Burkina Faso. Methods In an open-label controlled phase II study with 60 semi-immune adults with uncomplicated falciparum malaria in Nouna, north-western Burkina Faso, MB monotherapy (390 mg twice daily) was given sequentially to groups of 20 adults for 7 days (MB7), 5 days (MB5) and 3 days (MB3), respectively. The primary outcome was the rate of adequate clinical and parasitological response (ACPR) on day 28 of follow-up. Results Of the study population, 27/58 (47%) and 5/51 (10%) patients still had parasites on days 2 and 3, respectively, of follow-up resulting in 9/58 (16%) early treatment failures. By day 14, no recrudescence was observed but in 4/19 (MB5) and 2/20 (MB3) individuals by day 28. The PCR-corrected rate of ACPR was 72%, 58% and 85% in groups 7, 5 and 3, respectively, by per protocol analysis. Self-limiting dysuria was the most frequent adverse event. Conclusions MB acts slowly against the blood stages of P. falciparum. MB alone needs to be given for at least 7 days to be efficacious in the treatment of falciparum malaria but should be used in combination with a fast acting antimalarial.
Gesehen am 15.02.2023